Evaluasi Implementasi Program Pengendalian Kebisingan terhadap Penurunan Pendengaran pada Pekerja di PT “XYZ” - Dwi Enggar Widi Saptana; Mauliku, Novie Elvinawaty; Suhat, Suhat; Nugrahaeni, Dyan Kunthi (Yayasan Literasi Sains Indonesia, 2025)
Noise is one of the physical hazard factors in the work environment. Workers who are exposed to noise exceeding the Threshold Value above 85 db can cause permanent hearing loss. This can be overcome by optimizing the efforts of elimination, substitution, isolation, administrative control, and the use of PPE. Therefore, it is necessary to apply the Hearing Conservation Program. The purpose is to evaluate the implementation of the noise control program on hearing loss in workers at PT “XYZ”. The research design used a qualitative with an evaluative approach. The informants who informan were management, HSE, electrical technician, mechanic topside, and marine pumpman. Data collection techniques used in-depth interviews, observation, and document review, with instruments in the form of interview sheets, observation sheets, and checklist sheets. Data analysis was done by triangulation and data reduction. The results showed the company has a commitment and policy in an effort to reduce noise levels, but it hasn’t been maximized because elimination and substitution efforts cannot be applied, and it was found that there are still employees who are not fully compliant in using PPE in the workplace. Based on the results, it is concluded that the evaluation of the implementation of the noise control program on hearing loss in workers at PT XYZ has been running well. PT. XYZ demonstrates strong commitment to noise control, but faces challenges in implementation, including suboptimal noise control measures and incomplete PPE compliance.